2012
DOI: 10.11118/beskyd201205020153
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and natural antagonists of univoltine population of Ips typographus (Coleoptera, Curculionidae, Scolytinae) at epidemic level: a study from Šumava Mountains, Central Europe

Abstract: Lukášová K., Holuša J., Grucmanová Š. 2012: Reproductive performance of univoltine population of Ips typographus (Coleoptera, Curculionidae) at epidemic level in Central Europe: case study of small-scale and short-term bark beetles outbreak in the Šumava Mts. -Beskydy, 5 (2): 153-162Population of I. typographus was studied in one locality with small-scale and short-term outbreak distant from large-scale and long-term outbreak area by several hundred meters. In total, ten spruce trees infested by the spruce bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…do not contain -contrarily to data reported by Anderbrant (1990) -laid eggs from which larvae did not emerge or died at early stages. Our results correspond with those reported by Lukášová et al (2012) from another mountain area (Šumava, the Czech Republic), where the average number of eggs per female obtained from standing infested trees was 23.1. On the other hand, similar sampling done on lying trap trees (with weak or no defense mechanism) showed that the mean number of eggs laid by one female was 35 (Matoušek et al 2012), thus it was higher than that in natural infestations of standing trees, which supports the hypothesis about the reasons of differences observed.…”
Section: Infestation Characteristicssupporting
confidence: 92%
“…do not contain -contrarily to data reported by Anderbrant (1990) -laid eggs from which larvae did not emerge or died at early stages. Our results correspond with those reported by Lukášová et al (2012) from another mountain area (Šumava, the Czech Republic), where the average number of eggs per female obtained from standing infested trees was 23.1. On the other hand, similar sampling done on lying trap trees (with weak or no defense mechanism) showed that the mean number of eggs laid by one female was 35 (Matoušek et al 2012), thus it was higher than that in natural infestations of standing trees, which supports the hypothesis about the reasons of differences observed.…”
Section: Infestation Characteristicssupporting
confidence: 92%
“…The pathogen set in the analysed I. typographus from the wilderness area was very diverse with seven species compared to former studies in Austria and in the Czech Republic Lukášová et al 2012); from the well-known species only Menzbieria chalcographi (Weiser, 1955) originally described only in P. chalcographus, later in I. typographus (Wegensteiner & Weiser 2004) was not found in our study. Within previous surveys on pathogen occurrence in I. typographus from punctiform collections in the conservation forest area in the early 1990s, only G. typographi (in relatively high infection rates) and C. typographi (in low infection rates or absent) were recorded (Wegensteiner 1994; Wegensteiner et al 1996).…”
Section: Discussionmentioning
confidence: 52%
“…Studies on the pathogen occurrence in I. typographus-infested areas in managed and not-managed secondary spruce forests in Switzerland generally showed a much smaller range of pathogen species, and also that salvage logging operations do not lead to a depletion of the local pathogen species spectrum (Wegensteiner et al 2007). Lukášová et al (2012) reported three pathogen species only in I. typographus from the Šumava Mountains. Climatic conditions in different areas may favour or interfere with pathogen development, although almost nothing is known about the requirements of the bark beetle pathogens apart from entomopathogenic fungi (e.g., Mietkiewski et al 1994;in Butt et al 2001;in Roy et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In an initial analysis, 219 manuscripts from the Scopus database and 183 from the Web of Science database were considered. After articles that lacked information on type of management at the study locations (managed vs. unmanaged) were discarded, we acquired and analysed data from the following 10 publications: Haidler et al 2003;Händel et al 2003;Wegensteiner et al 2007Wegensteiner et al , 2014Wegensteiner et al , 2015Holuša et al 2009;Kereselidze et al 2010;Lukášová et al 2012Lukášová et al , 2013and Lukášová & Holuša 2015 (Table 1). Only data concerning living adult beetles from wind-thrown trees, horizontally lying trap trees, pheromone traps, trap logs, and standing trees were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The species composition and infection level of pathogens in bark beetle populations differ not only between locations but also between years in the same location (Wegensteiner et al 2014). The requirements for pathogen reproduction and the effects of pathogens on their hosts are poorly known for essentially all 10 pathogen species of I. typographus in Europe Lukášová & Holuša 2012;Wegensteiner et al 2015). In the case of microbial insect diseases, the pathogens invade and multiply in insects and spread to infect other individuals , but the pathogens lack the ability to actively move and actively seek hosts.…”
Section: Introductionmentioning
confidence: 99%